OTONOMI DAERAH DAN DESENTRALISASI DESA: Menuju Pemberdayaan Masyarakat Desa - Nadir, Sakinah (Jurnal Politik Profetik, 2016)
Villagers have been long marginalized and frequently treated as merely vote getters by outsiders’ power [the elites] to compete for their social and political support. This has been taking places for such a long time including during the time of Soeharto’s New Order. The legislation of Laws Number 22 Year 1999 on Regional Autonomy, and then the Laws Number 32 Year 2004 have provided better hope for a more democratic treatment for the villagers, particularly by the application of Village Autonomy [Otonomi Desa]. Village democracy through Village Autonomy is actually not a new concept in this country. Due to various obstacles, however, this sort of autonomy has never been successfully applied. Since the application of Laws Number 32 Year 2004, by the establishment of Village Democratic Board, it is hoped that village democracy may be successfully realized, not only on its formal aspects but also on its substantial ones.